Protective Role of Enalapril in Anthracycline-Induced Cardiotoxicity: A Systematic Review - Zhang, Yili; Liu, Junjie; Li, Yuan; Tan, Nannan; Du, Kangjia; Zhao, Huihui; Wang, Juan; Zhang, Jian; Wang, Wei; Wang, Yong (Frontiers in Pharmacology, 2020)
Background: Evidence of the preventive and therapeutic effects of enalapril on cardiotoxicity caused by chemotherapy needs to be further confirmed and updated. Methods: We performed a systematic review of studies from electronic databases that were searched from inception to January 29, 2019, and included relevant studies analyzing enalapril as a cardioprotective agent before or during the use of anthracyclines by oncology patients. Homogeneous results from different studies were pooled using RevMan 5.3 software. The Cochrane risk-of-bias tool was used to determine the quality of the studies. Results: We examined and screened 626 studies according to specific criteria and ultimately included seven studies that were relevant to the indicated topic. Among them, three studies reported the incidence of death during 6-month and 12-month follow-up periods. Six of the seven included studies showed possible positive results, suggesting that enalapril plays a cardioprotective role, while five of these studies showed that there was a significant difference in the left ventricular ejection fraction (LVEF) between an enalapril group and a control group (weighted mean difference (WMD) = 7.18, 95% CI: 2.49–11.87, I2 = 96%, P < .001). Moreover, enalapril was beneficial in reducing troponin I (TnI), creatine kinase myocardial band (CK-MB) and N-terminal pro-b-type natriuretic peptide (NT-proBNP) levels in cancer patients treated with anthracycline. Conclusions: Although a protective effect of enalapril on myocardial toxicity was observed in terms of the LVEF values and TnI, CK-MB and NT-proBNP levels, its use in the prevention and treatment of cardiotoxicity caused by anthracycline needs to be investigated by more scientific research.